THE SYSTEM OF DIVINE MANIFESTATION IN THE IBN ‘ARABIAN SCHOOL OF THOUGHT - Sayyed Ahmad Fazeli; Shiraz Agha (Sekolah Tinggi Filsafat Islam (STFI) Sadra, 2011)
One of the fundamental problems of Theoretical Mysticism is the explanation of the world as being something other than God after having accepted the Unity of Existence. This paper seeks to present, after having explained certain necessary premises, the theory of manifestation as one that can explain and analyze multiplicity.In this article we especially seek to solidify the relation of such claims to mystics in general and to the adherents of the Ibn ‘Arabian school of thought in particular. This is especially important because in some of the works of many specialists in this fi eld we fi nd that some unrealistic claims have been defi nitively attributed in to the Great Sheikh. The only way to counteract such false claims, in any field, including Theoretical Mysticism, is to make it binding upon ourselves to delve into the views of others in a cautious way. We must take the apparent meanings of the sayings of the mystics as a proof in this matter. Therefore the method of research of the writer of this article is to relate the sayings of the Great Sheikh and his commentators while commentating upon and analyzing them as well.